Synthesizing selenium- and silver-substituted hydroxyapatite-based bone grafts and their effects on antibacterial efficiency and cell viability - Aksakal, Bunyamin; Demirel, Mehtap; Sinirlioglu, Zeynep A. (WALTER DE GRUYTER GMBH, 2018)
Hydroxyapatite (HA)-based biografts with selenium (Se) and silver (Ag) substitutions were synthesized using the sol-gel method. The synthesized HA-based biografts at various Se and Ag quantity ratios (wt%) were characterized via Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM) and energy dispersive X-Ray spectroscopy (EDX). Escherichia coli (JM103) and Gram-positive Staphylococcus aureus (ATCC29293) bacteria were used for the cell viability tests by performing the MTT assay. During antibacterial tests, it was determined that the synthesized biografts showed significant antimicrobial activity on E. coli and S. aureus; however, some materials were effective on Gram-negative E. coli, but had no effect on Gram-positive S. aureus. In vitro cell viability tests revealed that some of the synthesized biografts such as H30Ag10Se15 and H40Ag20Se10 provided the highest cell viability rates compared to those in the control group.
Keywords: bone grafts; cell viability; hydroxyapatite; selenium; silver; NANOPARTICLES; INFECTIONS; Engineering; Medical Informatics